Financial Impact of a Long-Acting Injectable Cabotegravir/Rilpivirine Program: A Real-World Experience - Joshua P Havens; Jennifer O'Neill; Maureen Kubat; Jennifer M Davis; Nada Fadul; Shawnalyn W Sunagawa; Sara H Bares (Clinical Infectious Diseases, 2026)
Abstract Background Long-acting injectable (LAI) cabotegravir/rilpivirine (CAB/RPV) is an effective HIV treatment, but barriers, such as financial considerations limit implementation. Understanding the real-world financial impact is essential for program sustainability and equitable access. Methods This retrospective cohort study at the University of Nebraska Medical Center, Specialty Care Center (May 2022 to December 2024) evaluated people with HIV (PWH) receiving LAI CAB/RPV via buy-and-bill acquisition. We assessed annual staff time, program income (PI), and patient costs (PC). The primary endpoint was annual PI adjusted for staff time per patient compared to a modeled oral antiretroviral therapy (ART) comparator (bictegravir/emtricitabine/tenofovir alafenamide) using Wilcoxon Signed-Rank test. PI and PC were compared across study years and payer mix with Kruskal-Wallis test. Multivariate regression models explored factors predicting PI losses. Results The study included 110 PWH receiving 862 injections. LAI CAB/RPV required more annual staff time per participant than oral ART (7.4 hours vs. 3.7 hours). Median annual PI per participant hour managed was significantly lower for LAI CAB/RPV versus oral ART model across all study years (p<0.001). Despite this, the LAI program remained financially viable (median PI of $2,163/injection) with minimal PC; 91% of injections had $0 cost-sharing. PI losses occurred in 4.9% of injections and was associated with Medicaid coverage, lack of AIDS Drug Assistance Program (ADAP) coverage, and insurance changes. Conclusions Although LAI CAB/RPV requires double the staff time and generates less time-adjusted PI than oral ART, buy-and-bill LAI programs can remain financially viable. Payer mix and insurance stability are essential to ensuring sustainability and equitable access.